2020
DOI: 10.1063/5.0020766
|View full text |Cite
|
Sign up to set email alerts
|

637  μ W emitted terahertz power from photoconductive antennas based on rhodium doped InGaAs

Abstract: We investigate photoconductive terahertz (THz) emitters compatible with 1550 nm excitation for THz time-domain spectroscopy (TDS). The emitters are based on rhodium (Rh) doped InGaAs grown by molecular beam epitaxy. InGaAs:Rh exhibits a unique combination of ultrashort trapping time, high electron mobility, and high resistivity. THz emitters made of InGaAs:Rh feature an emitted THz power of 637 μW at 28 mW optical power and 60 kV/cm electrical bias field. In particular for a fiber coupled photoconductive emitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…A similar tendency can be seen in the evolution of femtosecond fiber lasers-based optoelectronics THz systems: Their emitted power has increased from several microwats [35] in 2010 to 637 µW in 2020 [37].…”
Section: Summary Systems Integration and Possible Extrapolations In Thz Imagingsupporting
confidence: 65%
See 2 more Smart Citations
“…A similar tendency can be seen in the evolution of femtosecond fiber lasers-based optoelectronics THz systems: Their emitted power has increased from several microwats [35] in 2010 to 637 µW in 2020 [37].…”
Section: Summary Systems Integration and Possible Extrapolations In Thz Imagingsupporting
confidence: 65%
“…These studies also indicated sensitivity of the proper materials design for effective THz emission in various types of TDS systems. Another recently study announced promising approach relies on MBE grown rhodium (Rh) doped InGaAs which exhibits a combination of ultrashort trapping time, high electron mobility, and high resistivity [37]. Because of these features, fiber coupled photoconductive THz emitters exhibit impressive characteristics: They delivered THz power amounts to 637 µW, the bandwidth extends up to 6.5 THz, and a record peak dynamic range reaches a value of 111 dB.…”
Section: Fiber Femtosecond Laser-based Thz Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both factors can be significantly improved. Similar EO generated frequency combs with a frequency coverage of around 1 THz have already been demonstrated [32], while pulsed PCAs emitting terahertz powers almost one order of magnitude higher than the used here have also been shown [16]. This would allow a thorough characterization of the phase noise evolution of the several thousands of modes composing the terahertz pulses generated by passively locked MLLs.…”
Section: Discussionsupporting
confidence: 62%
“…We employ two lines of an electro-optically (EO) generated frequency comb to produce a continuous wave (CW) terahertz signal that acts as a photonic local oscillator for the optoelectronic downconversion of the individual frequency components of a terahertz pulse. We therefore call this scheme Frequency Selective Optoeletronic Downconversion (FreSOD), feasible thanks to the recent developments in telecom-wavelength compatible PCAs [11]- [15]: when acting as emitters in pulsed operation, telecom-wavelength PCAs are now capable of delivering powers in excess of 0.5 mW [16], while CW receivers have shown noise equivalent powers (NEPs) as low as 1.8 fW/Hz [17]. For this particular implementation, we have used stateof-the-art ErAs:In(Al)GaAs PCAs, which have shown an excellent performance in both CW and pulsed operation.…”
Section: Introductionmentioning
confidence: 99%